ANALYSIS OF PHYSICAL INACTIVITY AMONG THE WORKING POPULATION OF RYAZAN REGION (ACCORDING TO THE STUDY MERIDIAN-RO) - Е. V. Filippov; V. S. Petrov (Klinicist)
Objective: to study the levels of PA and its relationship with other risk factors among the working population of the Ryazan Region. Material and methods. The MERIDIANRO study was conducted as a prospective cohort with crosssectional and retrospective study in cluded a sample of biochemical, ECG and a survey using a standardized questionnaire. The level of physical activity was assessed by ques tionnaire CINDI and then was revised by questionnaire IPAQ. In a study from 2011 it included 1,622 people (in 1220 – a city, 402 – village) aged 25–64 years (mean age – 43,4 ± 11,4 years), of which 42.6 % were male, 53.8 % – female. Results. The level of low PA in the Ryazan Region, measured by questionnaire IPAQ was 22.9 % (24.3 % in urban and 18.4 % in rural areas, p = 0.014). With multinomial logistic regression were established association between the PA and the low presence of higher education (OR 3.63; 95 % CI 2,26–5,85, p = 0.0001, Wald 28.172), smoking (OR 1.32, 95 % CI 1,01–1,72, p = 0.045, Wald 4,031) and elevated levels of Lp (a) more than 30 mg/dl (OR 1.38, 95 % CI 1,04–1,83, p = 0.024, Wald 5.119). It was also revealed a high demand for advice on improving the PA (74.5 %). Conclusion. The low level of PA in the Ryazan Region, as measured by the IPAQ questionnaire was 22.9 % (24.3 % in urban and 18.4 % in rural areas, p = 0.014), which is lower than Russian average. High demand for advice on improving the FA and created conditions for in creasing its level in the region indicate the need to intensify work among the population in this area.